Effectiveness of Land and Building Tax Collection in Region Palu City, Republic of Indonesia - M, Rudin; Bakarbessy , Maria Lea Frensy (Journal of Ecohumanism, 2025)
The purpose of this study is to determine and analyze the Effectiveness of Land and Building Tax Collection at the Palu City Regional Revenue Agency Office . This type of research is quantitative research. The data analysis technique used is effectiveness analysis. The results of this study conclude; (1) Land and Building Tax Collection at the Palu City Regional Revenue Agency Office is in the very effective criteria. (2) Supporting factors in the Land and Building Tax Collection of Palu City are: (a) Investment development in Palu City continues to increase so that Land and Building Tax Collection revenues continue to increase every year . (b) Supporting facilities are in accordance with taxation standards . ( 3) Inhibiting Factors in Land and Building Tax Collection Revenues are: (a) There is no awareness of all taxpayers to pay Land and Building Tax Collection which is their obligation as citizens of the Unitary State of the Republic of Indonesia. ( b) There is no similarity in Land and Building Tax Collection data at several agencies such as the Samsat Office, Regional Revenue Agency, Land, District Offices and Village Offices in the Palu City Area. (c) Limited human resources in terms of quantity.